Phytosociological and ecological discrimination of Mediterranean cypress ('Cupressus sempervirens') communities in Crete (Greece) by means of pollen analysis - López-Sáez, José Antonio; Glais, Arthur; Tsiripidis, Ioannis; Tsiftsis, Spyros; Sánchez-Mata, Daniel; Lespez, Laurent (Mediterranean Botany, 2019)
Sixty modern surface samples collected from mosses in different cypress forest communities (Cupressus sempervirens L.) on the island of Crete (Greece) were analysed for their pollen content. The samples were taken from six different cypress phytosociological associations between 23 and 1600 m asl, and fall within distinct rainfall and temperature regimes. The aims of this paper are to provide new data on the modern pollen rain from the Aegean islands, and to perform these data using multivariate statistics (hierarchical cluster analysis and canonical correspondence analysis) and pollen percentages. The discrimination of pollen assemblages corresponds to a large extent to the floristic differentiation of Cupressus sempervirens forest vegetation and indicates the existence of three new associations.